The Influence of Green Supply Chain Management on Environmental Entrepreneurship through Waste Management and Green Innovation - Debby Sri Haryanti; Gatri Lunarindiah; Wahyuningsih Santosa; Ratna Darasih (Manunggal Halim Jaya, 2026)
This study aims to analyze the effect of Green Supply Chain Management on Environmental Entrepreneurial Performance, mediated by Waste Management and Green Innovation in cement manufacturing companies. A total of 205 respondents participated in this study, consisting of managers, supervisors, and operational staff operating in the Citeureup area, Bogor Regency. Data were collected through questionnaire distribution using a non-probability sampling technique with a purposive sampling approach. The collected data were analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS 4.0 software. The results indicate that: (1) Green Supply Chain Management has a positive effect on Waste Management, (2) Green Supply Chain Management has a positive effect on Green Innovation, (3) Green Supply Chain Management has a positive effect on Environmental Entrepreneurial Performance, (4) Waste Management has a positive effect on Environmental Entrepreneurial Performance, (5) Green Innovation has a positive effect on Environmental Entrepreneurial Performance, (6) Green Supply Chain Management has a positive effect on Environmental Entrepreneurial Performance through the mediation of Waste Management, and (7) Green Supply Chain Management has a positive effect on Environmental Entrepreneurial Performance through the mediation of Green Innovation.